ANALYSIS OF STUDENTS’ ERRORS IN SOLVING STORY PROBLEMS ON RELATIONAL MATERIAL BASED ON POLYA STAGES - Siti Nurhalimah; Nofriyandi Nofriyandi; Dedek Andrian; Astri Wahyuni (Mathematics Research and Education Journal, 2025)
Abstract: This study aims to analyze errors using Polya's stages carried out by female students in solving story problems on the topic of relations. This study is a Qualitative study with a descriptive approach. The subjects of the study were 30 students of class VIII of SMP AL-FARUQI. The data collection technique used written tests and interviews. The data analysis technique was carried out through several stages, namely reducing data, presenting data and drawing conclusions. The results showed that the percentage of errors in understanding the problem was 50% with a moderate category, errors in making plans were 47.7% with a moderate category, errors in implementing plans were 63.3% with a high category, and errors in rechecking were 26.7% with a low category. The most common error made by female students was the error in implementing plans of 63.3%.